2019
DOI: 10.1088/1742-6596/1363/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kemiri Sunan (Reutealis trisperma Blanco) Seed Oil Nanoemulsion as insecticide against Planococcus minor (Hemiptera: Pseudococcidae)

Abstract: Estate commodities and flowering plants are mostly attacked by Planoccocus minor. Nowadays, botanical pesticide nanoemulsion technology is developing to be used to control insect pests. To evaluate the kemiri sunan seed oil nanoemulsion as insecticide against P.minor was the objective of this study. Completely Randomized Design (CRD) with four replication was used on the kemiri sunan evaluation test. Each replication consist of seven concentration (0,2%; 0,39%; 0,78%; 1,56%; 3,13%; 6%; and water as control). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The nanoemulsion showed promising efficacy, achieving an LC 50 value of 0.09% within 5 days post-treatment, with an LT 50 ranging from 3 to 7 days. 172 Seugling et al synthesized a larvicidal nanoemulsion containing Baccharis dracunculifolia oil through high-pressure homogenization and assessed its efficacy against Cochliomyia hominivorax . The herbal nanoformulation demonstrated a droplet size of 178.60 nm, a PDI of 0.226, a zeta potential of −35.40 mV, and an LD 50 value of 7.4% (w/v).…”
Section: Nanoemulsions: Transformative Insecticidal Formulation For T...mentioning
confidence: 99%
“…The nanoemulsion showed promising efficacy, achieving an LC 50 value of 0.09% within 5 days post-treatment, with an LT 50 ranging from 3 to 7 days. 172 Seugling et al synthesized a larvicidal nanoemulsion containing Baccharis dracunculifolia oil through high-pressure homogenization and assessed its efficacy against Cochliomyia hominivorax . The herbal nanoformulation demonstrated a droplet size of 178.60 nm, a PDI of 0.226, a zeta potential of −35.40 mV, and an LD 50 value of 7.4% (w/v).…”
Section: Nanoemulsions: Transformative Insecticidal Formulation For T...mentioning
confidence: 99%
“…Additionally, the insecticidal activity against several species of mealybugs was also demonstrated by different aromatic essential oils. (Cloyd et al, 2009;Karamaouna et al, 2013, Peschiutta et al, 2017, Erdemir and Erler, 2017, Mostafa et al, 2018, Prabowo and Damaiyani, 2019, Mwanauta et al, 2021, Saad et al, 2021and Brahmi et al, 2022 have been reported.…”
Section: Essential-oils Effect On F Virgata: Toxicity Of Formulated E...mentioning
confidence: 99%
“…Several plant-derived essential oils of Acorus calamus , Aegle marmelos , Cedrus deodara , Mentha piperita , Mentha spicata , Murraya koenigii , and Tagetus minuta were reported to have insecticidal activities against various insect pests in previous studies ( Reddy et al., 2016 ; Jayaram et al., 2022a ). Additionally, the homogeneous or heterogeneous blends of essential oils also revealed that the insecticidal activities against various species of mealybugs, including Pseudococcus calceolariae ( Tacoli et al., 2018 ), Planococcus citri ( Cloyd et al., 2009 ; Erdemir and Erler, 2017 ), Planococcus ficus ( Karamaouna et al., 2013 ; Peschiutta et al., 2017 ; Tacoli et al., 2018 ; Brahmi et al., 2022 ), Pseudococcus longispinus ( Hollingsworth and Hamnett, 2009 ; Tacoli et al., 2018 ), Paracoccus marginatus ( Mwanauta et al., 2021 ), Planococcus minor ( Prabowo and Damaiyani, 2019 ), Phenacoccus solenopsis ( Mostafa et al., 2018 ; Saad et al., 2021 ), and Pseudococcus viburni ( Ramzi et al., 2017 ) have been reported earlier. Essential oils often consist of a mixture of different biological compounds or phytochemicals with varied polarity, and separating them is still a significant challenge ( Sasidharan et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%